2021
DOI: 10.3390/ma14040820
|View full text |Cite
|
Sign up to set email alerts
|

Selectivity of Mixed Iron-Cobalt Spinels Deposited on a N,S-Doped Mesoporous Carbon Support in the Oxygen Reduction Reaction in Alkaline Media

Abstract: One of the practical efforts in the development of oxygen reduction reaction (ORR) catalysts applicable to fuel cells and metal-air batteries is focused on reducing the cost of the catalysts production. Herein, we have examined the ORR performance of cheap, non-noble metal based catalysts comprised of nanosized mixed Fe-Co spinels deposited on N,S-doped mesoporous carbon support (N,S-MPC). The effect of the chemical and phase composition of the active phase on the selectivity of catalysts in the ORR process in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 64 publications
0
7
0
Order By: Relevance
“… [8] In addition they showed the influence of composition and especially phase purity for the selectivity and activity of mixed iron cobalt spinels. [9] Using systematic cation substitution and tuning of the catalysts mesostructure with constant cation ratios, we herein exploit and extend this powerful approach to different oxygen evolving reactions.…”
Section: Introductionmentioning
confidence: 99%
“… [8] In addition they showed the influence of composition and especially phase purity for the selectivity and activity of mixed iron cobalt spinels. [9] Using systematic cation substitution and tuning of the catalysts mesostructure with constant cation ratios, we herein exploit and extend this powerful approach to different oxygen evolving reactions.…”
Section: Introductionmentioning
confidence: 99%
“…We specifically employed Pd, Ag, PdAg, and (MnCo) 3 O 4 as cathode catalysts to investigate the potential of oxygen radicals formed in different classes of catalysts. These catalysts are chosen as they have relatively high activities as cathodes in AEMFCs, , and they are significantly different.…”
Section: Introductionmentioning
confidence: 99%
“…Anion-exchange membrane fuel cells (AEMFCs) are regarded as a promising fuel cell technology because of their significant potential to replace the current expensive proton-exchange membrane fuel cell (PEMFC). Recently, AEMFCs achieved remarkable power densities with high voltage efficiencies, which makes the technology a serious contender for matured PEMFCs. Additionally, AEMFCs provide the opportunity to incorporate platinum group metal (PGM)-free catalysts into the electrodes, as well as a greater variety of low-cost polymers for use as membranes . In spite of these benefits, major challenges still need to be addressed before this technology can be utilized in practical applications.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have found that heteroatoms, such as N, P, S, O, B and so on, can significantly improve the electronic conductivity and electrocatalytic activity due to the altered electroneutrality and asymmetry of charge distribution around adjacent carbon atoms. [11][12][13][14] For example, due to the high electronegativity of oxygen, O-doping has been widely demonstrated to effectively tune the electronic structure of carbon and thus activate its electrocatalytic activity. [15][16][17] The current study shows that combining metal-based electrocatalysts with O-doped graphite layers can further improve the electrocatalytic activity.…”
Section: Introductionmentioning
confidence: 99%